Decentralization and local development in Algeria: Challenges, achievements, and future directions - KARA, Aldjia-Souad (The International tax journal, 2025)
Decentralization is a key institutional mechanism for fostering local development, as it promotes local democracy and establishes an enabling framework for grassroots initiatives, allowing local actors to address their challenges and enhance their living conditions. In Algeria, the decentralized system was implemented to overcome the limitations of top-down development policies and to facilitate local development projects through the active participation of various stakeholders. Nevertheless, numerous shortcomings persist within Algerian local authorities. This study aims to identify the origins of these shortcomings by analyzing the practices of local authorities and their engagement in the local development process.